Impact of land use and land cover changes on carbon storage in rubber dominated tropical Xishuangbanna, South West China. Issue 1 (1st January 2021) - Sarathchandra, Chaya; Alemu Abebe, Yirga; Worthy, Fiona Ruth; Lakmali Wijerathne, Iresha; Ma, Huaixia; Yingfeng, Bi; Jiayu, Guo; Chen, Huafang; Yan, Qiaoshun; Geng, Yanfei; Weragoda, Dayani S.; Li, Li-Li; et al.
ABSTRACT: Land use and land cover (LULC) play a significant role in carbon regulation. South-China accounts for 65% of China's carbon sink. In Xishuangbanna (South-China), rubber is expanding rapidly creating an urgent need to understand and monitor LULC change and how spatial variation affects carbon storage (CS). This is vital for the formation and implementation of better land use management practices. We studied LULC changes of 22-year period; addressing how these changes have affected the CS. We quantified LULC changes between1988 and 2010 using remote sensing methods and calculated CS changes using InvEST. Results showed that between 1988 and 2010, the rate of deforestation accelerated to 203.2 km 2 y −1 and 23% of forest were lost. Conversion of natural forest to rubber was responsible for 78% of this deforestation. Rubber expansion rate was 153.4 km 2 y −1 . Changes to LULC drove a temporal CS reduction 0.223 Tg C/km 2 . Local stakeholders have strong economic interest in converting land to more profitable plantations. Government efforts is required to control land conversion through new policies and incentives to retain natural forest. Assessment of specific potential land use change will be required to avoid promoting the conversion of high carbon storage land uses to low carbon storage land uses.